Winter sleep : a hibernation story - Taylor, Sean, 1965-; Morss, Alex (words & pictures, an imprint of The Quarto Group, 2019)
"Follow a child and his grandma through a winter landscape to explore how the Earth goes to sleep for winter. Spot the sleeping animals as the tale unfolds, then learn about their hibernation habits from the information pages at the end."--Amazon.com.